Rebuilding after Displacement: A Skills Competency Audit of Built Environment Professional Documentation - Carmichael, Andrew; Villalba-Romero, Felix; Liyanage, Champika (MDPI, 2022)
The displacement of people, caused by disasters, conflicts, and oppression, is a growing global problem, placing significant burdens on both the displaced and their hosts. The built envi‐ ronment is key to providing essential support and a sustainable future for these communities. This paper describes an audit of the competencies identified in built environment professional documen‐ tation and its mapping against the competencies determined as being relevant to rebuilding after displacement. Following a step‐by‐step methodology, an analysis of the built environment sector of four nations enables the identification of the current state of professional competencies through an in‐depth review of their published standards. These results are compared with a framework of standards that would maximise the potential of the sector in offering support. It is also identified where there is alignment between existing and ideal competencies, and where there are gaps in provision. Finally, a criticality analysis offers both sector‐wide and professional role review. This could help direct the efforts of policy makers, education providers, and the sector itself towards the most effective responses to displacement challenges
Keywords: Edificios - Reconstrucción y reparación - Auditoría; displacement; rebuilding; built environment; competencies; skills; professional capacities